MBCL-43. PROGNOSTIC FACTORS FOR OVERALL SURVIVAL AFTER RECURRENCE IN CHILDHOOD MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Huybrechts, Sophie; Chivet, Anaïs; Leys, Christophe; Varlet, Pascale; Tauziede-Espariat, Arnault; Puget, Stéphanie; Guerrini-Rousseau, Léa; Grill, Jacques; Dufour, Christelle
Abstract: PURPOSE: To identify prognostic factors for overall survival (OS) after recurrence in childhood medulloblastoma (MB). PATIENTS AND METHODS: Consecutive patients with MB treated at Gustave Roussy from 2007 to 2015 were retrospectively reviewed. Central histopathological review and molecular subgrouping are ongoing. RESULTS: Among our cohort of 131 patients, recurrence occurred in 46 children (35%) at median time of 13.5 months (range, 1-88 months). The pattern of recurrence was local in 9 patients, metastatic in 21 and synchronous metastatic and local in 16 patients. One, 3 and 5-year OS from recurrence were 44.7 ± 0.75%, 30.5 ± 0.86% and 25.4 ± 0.85%, respectively. Patients with late recurrence (time from diagnosis until recurrence ≥ 12 months) had a better outcome with a median survival after recurrence of 27 months (95%-CI, 7.67-46.32) compared to those with shorter time to relapse (median of 2 months; 95%-CI, 0.57-3.42). The variables influencing survival after recurrence were time to relapse, histopathological subtype and pattern of relapse/progression. Adjusting for time to relapse, multivariate analysis showed that age at diagnosis (< or > 5 years) was not a significant predictor for OS after recurrence. CONCLUSION: This study confirmed poor survival of patients with recurrent MB, particularly for those who relapse within 12 months after diagnosis. Yet patients with recurrence beyond 1 year have better outcome and may benefit from new therapies.